An Unusual Neurological Form of Acute Intussusception in an Infant: Late Diagnosis and Management - Ouidad Louachama; Noureddine Rada; Ghizlane Draiss; Karima Fouraiji; Mohamed Ouled Saiad; Mohamed Bouskraoui (Case Reports in Pediatrics)
Acute intussusception is one of the most common causes of intestinal obstruction in infants and small children and involves the invagination of one bowel segment into another. The clinical signs can be deceptively misleading when there is only one symptom or when an unusual symptom is in the foreground, especially in infants less than 1-year-old. We report a case of an infant with an acute intussusception where the neurological symptoms are predominant. The neurological form is the expression of major vascular narrowing of the collar of the intestinal intussusception; this form is rare and misleading and can be responsible for a delayed diagnosis.